Perceptions of Violent National-Political Protest among Arabs Living in Israel: A Pilot Study - Cohen-Louck, Keren (International journal of offender therapy and comparative criminology, 2021)
This pilot study examines the perceptions of Arabs living in Israel (ALI) regarding violent national-political protests (VNPP). ALI, exposed to VNPP by organizations of their own ethnic minority, are trapped in a political and cultural conflict between their state and their nation. Qualitative analysis of semi-structured interviews with 15 Muslim ALI identified four possible groups presenting four types of VNPP perceptions: (a) justifiers, who regard VNPP as a legitimate means of protecting the Palestinians and who profess Palestinian identity; (b) opponents, who strongly condemn VNPP and who profess Israeli identity; (c) those understanding but disagreeing with VNPP, professing a dual Palestinian-Israeli identity; and (d) the ambivalents, representing people with internal conflicts and mixed feelings regarding the Palestinian VNPP and their own identity. The study contributes to the understanding of how a group of ALI perceives the Palestinian VNPP, and implies that this population consists of different groups, each with its own unique identity.